2022
DOI: 10.1177/09721509221128637
|View full text |Cite
|
Sign up to set email alerts
|

Are ESG Disclosures Value Relevant? A Panel-Corrected Standard Error (PCSE) Approach

Abstract: Due to rising sustainability concerns across the globe, corporations are now offering voluntary environment, social, and governance (ESG) information to serve stakeholders’ interests. These voluntary ESG disclosures aid investors in making investment decisions by evaluating the firms’ sustainability. However, ESG reporting is still in its infancy and there are no regulatory standards; consequently, it is crucial to understanding the value relevance of ESG disclosures. Using panel corrected standard errors (PCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Board characteristics play a crucial role in influencing ESG disclosure practices. Research has shown that board diversity, including gender diversity, is positively associated with ESG disclosure (Manita et al, 2018;Masi et al, 2021;Nicolò et al, 2021;Wasiuzzaman & Subramaniam, 2023) According to legitimacy theory, firms with poor sustainability performance may strategically use additional sustainability disclosures to influence the perception of market participants and maintain their legitimacy (Abd-Elmageed, 2021;Kumawat & Patel, 2022). This aligns with the notion that organizations engage in ESG disclosure to mitigate concerns and maintain their legitimacy (Abd-Elmageed, 2021).…”
Section: Literature Reviewmentioning
confidence: 90%
“…Board characteristics play a crucial role in influencing ESG disclosure practices. Research has shown that board diversity, including gender diversity, is positively associated with ESG disclosure (Manita et al, 2018;Masi et al, 2021;Nicolò et al, 2021;Wasiuzzaman & Subramaniam, 2023) According to legitimacy theory, firms with poor sustainability performance may strategically use additional sustainability disclosures to influence the perception of market participants and maintain their legitimacy (Abd-Elmageed, 2021;Kumawat & Patel, 2022). This aligns with the notion that organizations engage in ESG disclosure to mitigate concerns and maintain their legitimacy (Abd-Elmageed, 2021).…”
Section: Literature Reviewmentioning
confidence: 90%
“…However, based on the results of the Wooldridge Test to detect autocorrelation and the Modified Wald Test to detect heteroscedasticity in the estimated regression model, it was found that there were problems of autocorrelation and heteroscedasticity. Therefore, panel corrected standard error (PCSE) was conducted to address the autocorrelation and heteroscedasticity issues (Kumawat & Patel, 2022;Minh Ha et al, 2021;Neves et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…PCSEs were preferred over separate OLS due to their superior performance when the error terms in the equations are correlated, known as contemporaneous correlation. This method has been proven effective by Kumawat and Patel [54] and Wang, et al [55]. STATA software was used for data analysis to take advantage of its consistency, detailed output documentation, and advanced research methodology.…”
Section: Methodsmentioning
confidence: 99%